Crisis of Spirituality and Rationality Balance in Islamic Education: Philosophical Analysis of K.H. Ahmad Dahlan's Educational Thought - Eko Ngabdul Shodikin; Sa'adi Sa'adi; Aji Nugroho; Naila Intania (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2025)
This research aims to philosophically analyze K.H. Ahmad Dahlan’s educational thought as a solution to the crisis in balancing spirituality and rationality within Islamic education. This crisis originates from the dichotomy between religious sciences (ulum ad-din) and general sciences (ulum al-kaun), which leads to value disorientation and weak integration within the Islamic education system. The study uses qualitative methods with a library research design and a hermeneutic-philosophical analysis approach. Data is obtained from the works of K.H. Ahmad Dahlan, biographical literature, and relevant previous research. Analysis is conducted through data reduction, thematic categorization based on ontological, epistemological, and axiological dimensions, and the interpretation of meaning using the framework of educational philosophy. The study reveals that K.H. Ahmad Dahlan developed an integrative educational philosophy that rejects scientific dualism and emphasizes the unity of revelation and reason. Ontologically, humans are viewed as spiritual-rational beings; epistemologically, knowledge derives from revelation and empirical reality; axiologically, knowledge must be realized in social practice. The novelty of this research lies in the systematic reconstruction of Dahlan's educational philosophy as a conceptual model relevant for the reform of modern Islamic education. This thought offers an integrative paradigm for developing value-based curricula, spiritual-digital literacy, and transformative social learning.